KARAKTERISTIK PENDERITA HIPERTENSI DI PUSKESMAS TITI PAPAN KECAMATAN MEDAN DELI TAHUN 2012 - drh.Rasmaliah, Mkes - -; drh.Hiswani.M.kes - -; rio - iskandar (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Abstract Hypertension is one of the degenerative diseases that a public health problem and a leading cause of death and morbidity are high in Indonesia and often appear without symptoms. Hypertension is caused by many factors, such as smoking, drink alcohol, drink coffee, stress and many more. In Indonesia, the prevalence of hypertension ranged from 30.7%. Based on the profile of the North Sumatra Provincial Health Office in 2008 which refers to the results Riskesdas 2007 in North Sumatra, from 10 types of non-communicable diseases is known that the prevalence of hypertension was ranked the fourth highest proportion of 5.8%. This study aims to determine how the characteristics of patients with hypertension in the Health Center Titi Papan Deli Medan District in 2012. Type of research is a descriptive study design case series. The samples size in this study were 258 men who comprised 98 (38.0%) men and 160 (62.0%) women. This study uses secondary data collection were obtained from patients with hypertension status card in Titi Health Center Board in 2012. Processing data using SPSS version 15.0 and statistical analysis using Chi Square. From the analysis using a statistical test Chi Square test is obtained there is no significant relationship between sex (p = 0.483) and occupation (p = 0.360) with the degree of hypertension by Chi Square test. While statistical analysis of age, education and place with the degree of hypertension can not be done because there are expected cell count of less than 5. To the community health center to check the blood presure of each patient aged >20 years old, every who go to the community health center. Keywords: Characteristics of patients with hypertension